Virtual monoenergetic reconstruction of contrast-enhanced dual energy CT at 70 keV maximizes mural enhancement in acute small bowel obstruction. Issue 5 (May 2016) - Darras, Kathryn E.; McLaughlin, Patrick D.; Kang, Heejun; Black, Brian; Walshe, Triona; Chang, Silvia D.; Harris, Alison C.; Nicolaou, Savvas
Graphical abstract: Highlights: A new CT technique for identifying ischemia in small bowel obstruction is proposed. Virtual monoenergetic imaging at 70 keV increases conspicuity of small bowel mucosa. Contrast resolution is better on VMI at 70 keV when compared to conventional CT. Equal diagnostic acceptability noted between the VMI at 70 keV and conventional CT. Increased diagnostic confidence reported on the VMI at 70 keV images. Abstract: Purpose: In patients with small bowel obstruction (SBO), it is challenging to detect early ischemia. The purpose of this study is to evaluate the quantitative and qualitative benefits of virtual monoenergetic image (VMI) reconstruction in the assessment of small bowel mural enhancement on dual source dual energy computed tomography (CT) scans of the abdomen. Materials and methods: Institutional review board approval was obtained, for this retrospective analysis. 72 consecutive patients with acute SBO were scanned using a second generation 128-slice dual source, CT system. Images were reconstructed at VMI energy levels from 40 to 110 keV in 10 keV increments and were analysed quantitatively and qualitatively. Contrast to noise ratios (CNR) and signal to noise ratios (SNR) for mural enhancement were recorded for all VMI datasets and compared to conventional polychromatic images (PCI) at 120 kVp. Subjective analysis of mural enhancement on VMI and PCI was performed by 3 blinded readers. Results: Optimal CNR values for small intestinal mural enhancement were observed at 70 keV. Qualitative assessment revealed that there was no statistical difference in diagnostic accuracy between VMI and PCI. All readers reported improved confidence when assessing the contrast enhancement on the 70 keV VMI dataset and in our series, 2 additional cases of ischemia were identified on this reconstruction. Conclusion: Contrast-enhanced dual source dual energy CT with VMI reconstruction at 70 keV maximizes the CNR of small bowel mural enhancement and increases the overall diagnostic confidence in assessing mural enhancement in patients with SBO.